2009
DOI: 10.1007/s10495-009-0353-7
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis-inducing factor plays a critical role in caspase-independent, pyknotic cell death in hydrogen peroxide-exposed cells

Abstract: It has been proposed that continuously generated hydrogen peroxide (H(2)O(2)) inhibits typical apoptosis and instead initiates an alternate, apoptosis-inducing factor (AIF)-dependent process. Aside from the role of AIF, however, the detailed morphological characterization of H(2)O(2)-induced cell death is not complete. This study examined the cellular mechanism(s) by which the continuous presence of H(2)O(2) induces cell death. We also further analyzed the precise role of AIF by inhibiting its expression with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 47 publications
(68 reference statements)
4
52
0
Order By: Relevance
“…Cdk5 activation is increased by cleavage of its regulatory protein p35 to p25 in response to neurotoxic insults. 37,38 Given the emerging link between both Cdk5 and tAIF and oxidative stress-induced neuronal cell death, [39][40][41][42] we hypothesized that oxidative stress-induced Cdk5 activation triggers neuronal cell death by inhibiting CHIP-mediated degradation of tAIF. In primary cultured Figure 3 Cdk5 negatively regulates CHIP-mediated tAIF degradation via UPS.…”
Section: Resultsmentioning
confidence: 99%
“…Cdk5 activation is increased by cleavage of its regulatory protein p35 to p25 in response to neurotoxic insults. 37,38 Given the emerging link between both Cdk5 and tAIF and oxidative stress-induced neuronal cell death, [39][40][41][42] we hypothesized that oxidative stress-induced Cdk5 activation triggers neuronal cell death by inhibiting CHIP-mediated degradation of tAIF. In primary cultured Figure 3 Cdk5 negatively regulates CHIP-mediated tAIF degradation via UPS.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we found that the continuous presence of H2O2 induces mitochondrial stress and subsequent cell death in a time-and dose-dependent manner (9). To determine the role of JunB in H2O2-induced cell death, we transfected cells with JunB-specific siRNA.…”
Section: Inhibition Of Junb Expression By Sirna Transfection Promotesmentioning
confidence: 99%
“…Whole cell lysates were made in a lysis buffer as described previously (9,11), after which the protein content was quantified according to the Bradford method (28). Nuclear and mitochondrial fractions were prepared as described elsewhere http://bmbreports.org (9).…”
Section: Western Blot Analysismentioning
confidence: 99%
See 2 more Smart Citations